Laminar Natural Convection Study in a Horizontal Half- Elliptical Enclosure Using Heater on Horizontal Wall - Abdelkarim, Bouras (Université de M'sila, 2019)
A numerical analysis of laminar natural convection in a horizontal annulus between an internal heated plane and an external cold half-elliptical was investigated using approximation of Boussinesq. Both internal and external walls are maintained at the constant temperature and air is the working fluid. Numerical solutions are obtained using a commercial computational fluid dynamics package, FLUENT, using the finite volume method. Effects of the Rayleigh number, Rat, on the Nusselt number, Nu, as well as velocity and temperature fields are investigated for the range of Rat from 1.0 103 to 5.0 105. The results show that for a small thermal Rayleigh number, the heat transfer within the annulus is essentially controlled by the conduction process. As the thermal Rayleigh number increases (Rat ≥ 104), the role of convection becomes predominant. Also the heat transfer rate increases. The aim of this study is to observe the effects of thermal Rayleigh numberon the structure of the flow and the distribution of the temperature.
Keywords: Thermal transfer, Natural convection, Circular and half-elliptical, Multicellular flow, Laminar flow, Steady flow